Clustering and estimating fish fingerling abundance in a tidal river in close ploximity to a thermal power plant in Southern Thailand. (April 2018) - Chesoh, S; Lim, A; Luangthuvapranit, C
Abstract: This study aimed to cluster and to quantify the wild-caught fingerlings nearby thermal power plant. Samples were monthly collected by bongo nets from four upstream sites of the Na Thap tidal river in Thailand from 2008 to 2013. Each caught species was identified, counted and calculated density in term of individuals per 1, 000 cubic meters. A total of 45 aquatic animal fingerlings was commonly trapped in the average density of 2, 652 individuals per 1, 000 cubic meters of water volume (1, 235–4, 570). The results of factor analysis revealed that factor 1 was represented by the largest group of freshwater fish species, factors 2 represented a medium-sized group of mesohaline species, factor 3 represented several brackish species and factor 4 was a few euryhaline species. All four factor reached maximum levels during May to October. Total average numbers of fish fingerling caught at the outflow showed greater than those of other sampling sites. The impact of heated pollution from power plant effluents did not clearly detected. Overall water quality according the Thailand Surface Water Quality Standards Coastal tidal periodic and seasonal runoff phenomena exhibit influentially factors. Continuous ecological monitoring is strongly recommended.